The recycled polyethylene terephthalate (PET) bottles waste as a fine aggregate replacement in concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Othman, Nur Hawa; Ali, Maisarah (The Mattingley Publishing Co., Inc, 2020)
This research aims to study the potential of shredded PET bottles waste as a fine aggregate replacement in concrete. PET bottles waste was preferred because it is readily available, and it causes an environmental problem. The PET bottles waste was shredded into a fine particle. The size of fine particle is of similar size of the sand particle. It is partially replaced by sand with 0.5%, 1% and 1.5% in the concrete mix. This mix design method is referred from the Department of Environment (DOE), and the test is carried out for M30 grade concrete for 7-days,28-days, and 90-days. The performance of recycled PET bottles concrete was investigated based on experimental tests such as slump test, flexural strength test, and compressive strength test. The slump value of PET bottle concrete is similar to conventional concrete. Flexural strength and compressive strength increased for 90 days of curing for 0.5%,1%, and 1.5% substitution of shredded PET bottles aggregates by sand. For 7 days and 28 days strength is slightly more or less equal to conventional concrete. The application of this newly developed concrete material can be sustainable for the construction industries. It has the potential to improve the properties of concrete.